STUDI PEMANFAATAN ENERGI MATAHARI SEBAGAI PEMANAS AIR - Sidopekso, Satwiko (BERKALA FISIKA, 2011)
Using the principle of a box in a black body covered with glass crystal, Energy from the sun light which was emit thermal radiation energy of 1000 Watt/m2 at the day light under Standard Test Condition (STC), the head from the sun light will be speared in the box. Water from the storage tank will circulate without using a booster pump according to the principle thermoshipon to pass through the head collector pipes made of copper in a closed circulation and returned to the water storage tank. With water heating system is expected to have hot water with temperatures above 60o Celsius during the day. Key word : Solar Energy ; Head Collector; Thermoshipon.